The Effect of Collegial School Management on Improvement of Students’ skills - Xhomara, Nazmi (Pedagogika, 2019)
The study aims to investigate the effect of collegial school management on the prevention of disruptive behaviors and students’ life skills. A quasi-experimental research design, a structured questionnaire, and the cluster random samples were used in the study. It is found that school management increase the prevention of disruptive behaviors and students’ life skills, and collegial school management predicts the prevention of disruptive behaviors and students’ life skills.